Existe bolha no mercado imobiliário brasileiro? - Mário Jorge Mendonça; Adolfo Sachsida (Instituto de Pesquisa Econômica Aplicada (IPEA), 2012)
– This article verifies the occurrence of a real estate bubble in the Brazilian economy. Overall, our results suggest the existence of a bubble in the real estate sector of the economy. The Austrian School of economics provides a solid explanation to this phenomenon, which are reinforced by statistical techniques, suggesting the Federal government, with equivocate fiscal and monetary policy, as the main responsible for the creation of this problem.
Keywords: E31; E52; E62; C32; 330; real estate bubble; Austrian School; VAR models; monetary policy; fiscal policy; Immobilienmarkt; Spekulationsblase; Österreichische Schule; Brasilien